1997
DOI: 10.1017/s0033291797005321
|View full text |Cite
|
Sign up to set email alerts
|

Chronic medical conditions and mental health in older people: disability and psychosocial resources mediate specific mental health effects

Abstract: Background. This study describes the differences in psychological distress, disability and psychosocial resources between types of major medical conditions and sensory impairments (collectively denoted as CMCs); and tests whether disability and psychosocial resources mediate CMC-specific mental health effects.Methods. Data were obtained from a population-based, cross-sectional survey of 5078 non-institutionalized, late middle-aged and older Dutch persons. The predictors were 16 types of CMCs, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 55 publications
7
108
0
1
Order By: Relevance
“…A more realistic mediation scenario posits a reciprocal relationship between depression and condition-specific functional impairment. Nevertheless, our findings support a general conceptual model, suggested for conditions other than UI such as low vision, 20 arthritis, 21 or other chronic medical conditions, 22 that conditionspecific functional impairment mediates the relationship between a chronic medical condition and psychological distress.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A more realistic mediation scenario posits a reciprocal relationship between depression and condition-specific functional impairment. Nevertheless, our findings support a general conceptual model, suggested for conditions other than UI such as low vision, 20 arthritis, 21 or other chronic medical conditions, 22 that conditionspecific functional impairment mediates the relationship between a chronic medical condition and psychological distress.…”
Section: Discussionsupporting
confidence: 82%
“…19 Withdrawal from activities, even if self-imposed, may lead to feelings of loss of control and diminished life satisfaction. Previous research has suggested that condition-specific functional loss accompanying low vision, 20 arthritis, 21 or other chronic medical conditions 22 was associated with depression. However, no previous research has examined whether persons with UI associated with condition-specific functional loss are more likely to have depressive symptoms than persons who do not report condition-specific functional loss due to UI.…”
mentioning
confidence: 99%
“…They warrant expert assessment for depression or anxiety as this score is above`disorder likely' threshold. In comparison, Ormel [15] found that 24.5% of a large sample of chronic medical patients scored above 12 on the HADS. In common with most psychological screening instruments, the sensitivity of the HADS is excellent (100% in one study of medical patients [16]) but the specificity is less impressive (ranging from 73% in one study [6] to 94% in another [17]).…”
Section: Discussionmentioning
confidence: 93%
“…GLAS was a population-based prospective followup study of the psychological and social determinants of disease, functional disability, wellbeing and utilisation of care in older people [21,[23][24][25][26][27]. The primary objective of this study was to identify the psychosocial factors that influence the trajectory of QoL, independently or in interplay with diseaserelated factors.…”
Section: Methodsmentioning
confidence: 99%